Ferroptosis and pyroptosis in diabetes mellitus: emerging therapeutic potential of GLP-1 receptor agonists - Panou, Theodoros; Gouveri, Evanthia; Rizzo, Manfredi; Popovic, Djordje S.; Papanas, Nikolaos (Frontiers in Clinical Diabetes and Healthcare, 2025)
Ferroptosis and pyroptosis are two emerging forms of regulated cell death. The former encompasses cell death by excessive accumulation of lipid hydroperoxides in an iron-dependent way. The latter pertains to inflammation-associated cell death following activation of caspase-1, caspase-11/4/5 through gasdermin D (GSDMD). Recent evidence confirms the implication of ferroptosis and pyroptosis in diabetes mellitus (DM) and its complications, notably diabetic kidney disease (DKD), and also in metabolic-dysfunction associated liver disease (MASLD). The aim of this narrative review was to summarise current experimental evidence on the potential beneficial actions of glucagon-like peptide-1 receptor agonists (GLP-1RAs) in DM and diabetic complications via reduction of ferroptosis and pyroptosis. Data points to their therapeutic potential in DKD and MASLD. Treatment with GLP-1RAs was comparable with ferrostatin-1 (Fer-1), a well-known-ferroptosis inhibitor: ferroptosis-associated markers (e.g. Acyl-CoA Synthetase Long Chain Family Member 4, ASCL4) were decreased and factors alleviating ferroptosis were increased. Similarly, caspase-1, GSDMD, interleukin-1β (IL-1β) and/or nucleotide-binding oligomerization domain, leucine-rich repeat-containing receptor-containing pyrin domain 3 (NLPR3), which induce pyroptosis, were restored following GLP-1RAs therapy. The pleiotropic effects of GLP-1RAs included improvements in inflammatory markers, fibrosis-associated indices, mitochondrial ultrastructure and oxidative stress. Nevertheless, these positive effects mediated by GLP-1RAs are almost exclusively based on experimental models. Therefore, clinical trials are required to explore these promising outcomes in clinical practice.